Eça de Queirós e seu texto de imprensa 'Tema para versos I e II' (02 e 03/04/1893-Gazeta de Notícias): considerações - Feitosa, Rosane Gazolla Alves [UNESP] (My University, 2014)
Eça de Queirós published in Gazeta de Notícias, the text “Theme for verses I and II” in April 2nd and 3rd in 1893 . From part II, it was taken an excerpt and published as a short story under the title “The maid” when this text was a part of the book Short Stories (12 stories, some of them handwritten, from 1874 to 1897) gathered by his friend, Luís de Magalhães, and published in 1903, under the year of 1902. Since then, the text ”The maid” is present in many editons of Eça de Queirós’ short stories without any mention to its primary source, the newspaper Gazeta de Notícias (Rio de Janeiro), or even the other part of the text in which it was originally in. The objective of these short considerations is reflecting if the short story, known as “The maid”, should be read as an excerpt of the original text as it has been done since 1902, or it should be put in its original context, joining the two parts of the text “Theme for verses I and II”.

Eça de Queirós publicou na Gazeta de Notícias o texto “Tema para versos I e II” em 2 e 3/04/1893. Da parte II, foi retirado um trecho e este foi divulgado como conto, sob o título “A Aia”, quando passou a integrar o volume Contos (12 narrativas, algumas manuscritas, de 1874 a 1897), recolhida por seu amigo, Luís de Magalhães, e publicado em 1903, com data de 1902. Desde então, o texto “A Aia” está presente nas várias edições de contos de Eça sem fazer menção à sua fonte primária, jornal Gazeta de Notícias (Rio de Janeiro), nem ao restante do texto de qual fazia parte, originalmente. O objetivo destas breves considerações é refletir se a narrativa breve, divulgada como “A Aia”, deve ser lida como um excerto do texto original como vem sendo feito desde 1902 ou deveria ser inserida no seu contexto original articulando as duas partes do texto “Tema para versos I e II”.
Eça de Queiroz and his press text: “Topic for i and ii versus” (04/02/1893 and 04/03/1893 – Gazeta News): considerations
Keywords: The maid; Theme for verses I and II; Gazeta de Notícias; Eça de Queirós; Newspaper texts; A Aia; Tema para versos I e II; Gazeta de Notícias; Eça de Queirós; Textos de imprensa